Systematic study of a thulium-doped all-polarization maintaining modelocked fiber laser from a low to high fundamental repetition rate - Cuadrado Laborde, Christian Ariel (2025)
In this work, we present an experimental and theoretical study of a passivelymodelocked all-fiber laser that fully retains polarization with a fundamental repetition rateranging from 0.1 to 1 GHz. The whole cavity consists of a highly-Tm-doped fiber in tandemwith a passive fiber, both with polarization-maintenance, with a dichroic mirror on one end anda semiconductor saturable absorber mirror on the other. We experimentally characterized theoutput of this laser, which emits a train of transform-limited sub-picosecond light pulses aroundthe two microns. The high stability of this laser was also experimentally verified. Together withthis, a detailed theoretical model was developed, confirming the experimental results.